1-D WAVE PROPAGATION ANALYSIS USING NON - MASING GENERAL QUADRATIC/HYPERBOLIC (GQ/H) MODEL TO DETERMINE BASIN EFFECT CORRECTION FACTOR BASED ON 2-D WAVE PROPAGATION ANALYSIS DATA RESULT - Kurnia Jayanti, Harum
The basin effect is known to have influence on the earthquake response at the ground surface, especially at the edge of basin and will cause amplification of seismic waves in soft sediment deposits. The geometry of the basin greatly influences the resulting basin effect because the basin’s slope will trap body waves and cause stronger and longer earthquakes. Seismic studies are currently carried out using 1-D wave propagation analysis where the 1-D analysis gives different results from the 2-D analysis, especially at the edge of the basin due to the basin effect. The new soil model, General Quadratic/Hyperbolic (GQ/H), which overcomes the limitations of the previous soil model, Modified Kondner – Zelasko (MKZ), can represent small – strain nonlinearity of soft clay. Based on practical consideration, it is necessary to conduct a study to predict the correction factor between 1-D analysis and 2-D analysis to consider the basin effect. The aim of this final project is to determine the basin effect correction factor from 1-D analysis results based on the 2-D analysis results at the edge of the basin, to evaluate the effect of geometry (angle, width, and depth) of the basin, and to evaluate the spectral acceleration from the 1-D analysis results that use the Non – Masing General Quadratic/Hyperbolic (GQ/H) model. The 1-D analysis and modeling for the corresponding model uses DEEPSOIL with a various parameter variation, such as variations in Peak Ground Acceleration (PGA) of input motion, variations in angle and width of the basin, and variations in the ratio of depth and width of the basin (D/W). The results show that the correction factor in the basin edge is greater than in the middle zone of the basin due to the basin effect with varying influence of parameter variations on the correction factor. Selection of soil shear strength parameter greatly determines the surface response of soft clay soil. Spectral acceleration deamplification on the surface is found in all model variations.